FRONTEND DEVELOPMENT OF COURSE SCHEDULING SYSTEM INTEGRATED SIA AT ENGINEERING FACULTY UNIVERSITY OF JENDERAL SOEDIRMAN USING DEVOPS METHOD - Herfina Intan Yuanita; Bangun Wijayanto; Teguh Cahyono (Informatika, Universitas Jenderal Soedirman, 2022)
The Course Scheduling System is a website-based system that has the function of compiling course schedules at the Faculty of Engineering, Jenderal Sudirman University. This system is used by several users, namely Bapendik/admin and vice dean, while the results of the scheduling will be inputted into SIA and viewed by SIA users. This system has features to manage lecturer data, course data, room data, slot data, day data, and arrange course scheduling. Previously, the preparation of courses was still using the manual method, namely by entering the course data one by one. Based on the existing problems, the author tries to build a frontend of the Course Scheduling System to facilitate users in compiling a computerized and automatic course schedule through the system. The system is built using the DevOps development method and the javascript library, namely React Js. The results of system testing show that all functions on the system can run according to user needs.